El Excentrico, 1963-05-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
May 20, 1963 [20 de mayo de 1963], Ano 13, No 15. Cover has the photo of the little Fernandez Twins, with headline, "The Fernandez Twins - Cheaper by the Dozen - plus one."